2021
DOI: 10.3390/medicina57060633
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Causing Hypotension in Frail Geriatric Hypertensive Patients?

Abstract: Background: The association of coronavirus disease 2019 (COVID-19) with hypertension has been one of the frequently discussed topics in current studies since hypertension was identified as a risk factor for coronavirus disease. However, no studies seem to be focused on the BP (blood pressure) in patients with hypertension after COVID-19. Report: This report presents the cases of five frail geriatric patients (avg. age 78.3 (±6.4) years) with sarcopenia and controlled hypertension (office BP < 140 mmHg) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Koudelka et al reported the cases of five frail geriatric patients with sarcopenia and controlled hypertension who became hypotensive after COVID infection. They found that the previously well-established therapy was suddenly too intensive for those patients [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Koudelka et al reported the cases of five frail geriatric patients with sarcopenia and controlled hypertension who became hypotensive after COVID infection. They found that the previously well-established therapy was suddenly too intensive for those patients [43] .…”
Section: Discussionmentioning
confidence: 99%
“…The elderly are a group at high risk of being infected with Covid 19 because they have a decreased immune system which makes it easier for the virus to attack the respiratory system (Venugopal et al, 2020). In addition, the elderly also have an increased risk of getting Covid 19 because they have comorbidities (Viro et al, 2021), for example, disorders of the cardiovascular system such as hypertension (Koudelka & Sovová, 2021). The prevalence of hypertension increases with age which affects more than 50% of the elderly aged 60 years (Pan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Poor BP control status was also independently associated with higher risk. However, a recent study comparing BP < 130 mmHg with <140 mmHg reported that patients with BP < 130 mmHg treated with COVID-19 were associated with higher mortality, especially in geriatric patients [ 6 8 ] In the end, how is the BP target in COVID-19 patients still unclear.…”
Section: Introductionmentioning
confidence: 99%